Efficacy of Three Variants of Dioscorea bulbifera L. Leaf Extract as Termiticides to Control the Dry Wood Termites (Cryptotermes cynocephalus Light) - Oksari, Ade Ayu; Faridha, Faridha; Susanty, Devy; Rizki, Fathan Hadyan; Rohimatun, Rohimatun; Wanda, Irvan Fadli; Arinana, Arinana; Dadang, Dadang (AGRIVITA Journal of Agricultural Science, 2025)
The leaves of Dioscorea bulbifera L. have chemical compounds that have the potential as bioinsecticides. This study aims to determine the effectiveness of polar, semi-polar, and non-polar fractions in D. bulbifera leaf extract as bioinsecticides. The research design used was a Factorial, Completely Randomized Design consisting of two factors with five repetitions using the contact method against Cryptotermes cynocephalus. The first factor was the type of solvent: non-polar solvents, semi-polar solvents, and polar solvents. The second factor was concentration, with a range of 5%, 4%, 3%, 2%, and 1%. Based on the results, the D. bulbifera leaves in the polar fraction contain alkaloids, flavonoids, phenols, triterpenoids, and saponins. The semi-polar fraction contains alkaloids, phenols, and steroids. The non-polar fraction contains alkaloids, phenols, and triterpenoids. GC-MS identification showed 20 metabolite compounds as potential as botanical insecticides. The highest termite mortality was in the non-polar fraction, with a 4% concentration of 32.80% (equivalent to a corrected mortality of 27.58%). The semi-polar fraction (3.20 g and 15.10%) at a concentration of 5% (2.58 g and 12.19%), showed the best reduction in test weight and degree of damage. This result indicates that D. bulbifera is an effective bioinsecticide in the repellent group.